Membongkar Stereotipe: Peran Sosio-Antropologi dalam Mendorong Pemberdayaan Perempuan dan Mengatasi Pernikahan Dini - Inayah, Nafisah Widhah; Panggabean, Destyn; Yuliasari, Elly; Fadila, Rahayu Deka; Ningtyas, Rosalinda Syafira Cahya; Hinamalu, RR. Diana Septya Ningdyah Putri; ‘Aini, Ulya Qurrotul (Universitas Negeri Malang, 2024)
Background: Early marriage in Indonesia remains a serious issue with negative impacts on the health and well-being of women and the children born from these marriages. The role of socio-anthropology in promoting women's empowerment and understanding the distinctive features of wedding ceremonies can provide important insights in addressing this issue. Objectives: This study aims to analyze the role of socio-anthropology in dismantling gender stereotypes and promoting women's empowerment and addressing early marriage in Indonesia. Method: The method used is the literature review method. Data collection was carried out using journal articles obtained from scientific databases such as Google Scholar. The selected literature sources will be evaluated and analyzed, then will be compiled as discussion material for the preparation of the article. Results: Socio-anthropological analysis shows that gender stereotypes that trigger early marriage are linked to the construction of social norms, culture and traditions that significantly disadvantage women. A socio-anthropological strategy to address early marriage requires cooperation between stakeholders and a holistic approach that involves various aspects of community life.